Continuous walking and time- and intensity-matched interval walking: Cardiometabolic demand and post-exercise enjoyment in insufficiently active, healthy adults. Issue 1 (2nd January 2021) - Francis, Kate; Williamson, Tom; Kelly, Paul; Phillips, Shaun M.
ABSTRACT: We compared cardiometabolic demand and post-exercise enjoyment between continuous walking (CW) and time- and intensity-matched interval walking (IW) in insufficiently active adults. Sixteen individuals (13 females and three males, age 25.3 ± 11.1 years) completed one CW and one IW session lasting 30 min in a randomised-counterbalanced design. For CW, participants walked at a mean intensity of 65–70% predicted maximum heart rate (HRmax ). For IW, participants alternated between 3 min at 80% HRmax and 2 min at 50% HRmax . Expired gas was measured throughout each protocol. Participants rated post-exercise enjoyment following each protocol. Mean HR and V˙O2 showed small positive differences in IW vs. CW (2, 95%CL 0, 4 beat.min −1 ; d = 0.23, 95%CL 0.06, 0.41 and 1.4, 95%CL 1.2 ml.kg −1 .min −1, d = 0.36, 95%CL 0.05, 0.65, respectively). There was a medium positive difference in overall kcal expenditure in IW vs. CW (25, 95%CL 7 kcal, d = 0.58, 95%CL 0.33, 0.82). Post-exercise enjoyment was moderately greater following IW vs. CW (9.1, 95%CL 1.4, 16.8 AU, d = 0.62, 95%CL 0.06, 0.90), with 75% of participants reporting IW as more enjoyable. Interval walking elicits meaningfully greater energy expenditure and is more enjoyable than CW in insufficiently active, healthy adults.